The application of wadi’ah contract by some financial institutions in Malaysia - Ibrahim, Ahmad Basri; Mohd Noor, Azman; Sahrir, Muhammad Sabri (2012)
Islamic finance emancipated as a replacement for the conventional financial practices that aims only at profit making i.e. capitlist oriented finance. Although both are termed finance, but Islamic finance has two major distinguish features which are: the motive is not profit making only rather seeking the pleasure of Allah’s mercy in the hereafter. The second feature is the use of asset backed-up transactions and profit distribution system as agreed at fore hand. These features manifested in the dealings of the Islamic Financial Institutions (IFIs) established to excute the aims and objectives of Islam and Muslims as the vicegerent of Allah on earth and one who are bound by injunctions in all their transactions. In order to achieve these objectives Islamic banks have moved in an alternative bearing from the conventional banks in practices and brands of products. One of these products is rebranding of the conventional savings account with the Wadi‘ah account. Therefore, this paper aims at explaining the concept of wadi‘ah, the evidences of its legitimacy, conditions, prohibited elements in this transaction, its types and how its application in some financial institutions in Malaysia. Finally, we found out that, modern wadi‘ah took a different shape from the original wadi‘ah. While original wadi‘ah is based on Amanah (turst), contemporary wadi’ah is based on daman (liability) which is more or less loan.